Digestible lysine requirement of growing Finnish landrace x Yorkshire pigs determined by N-balance technique - Laurinen, Pasi; Suomi, Kaija; Näsi, Matti; Halonen, Heljä (CABI Publishing, 2000)
Digestible lysine requirements of growing pigs was determined using the N-balance technique. The basal diet consisted of barley and soyabean meal. Other diets were formulated by substituting basal diet with wheat starch or with synthetic amino acids and casein. Both castrated males and gilts improved N retention linearly by 2.5 g/d with 1 g increase in digestible lysine content, indicating a higher requirement than 10.6 g/fu (1 fu=9.3 MJ NE) in animals of 25-50 kg live weight. Retention of N also improved up to the highest level for animals between 50 and 105 kg live weight, but only by 1.7 g/d per g digestible lysine/fu.
Keywords: Ko; sika; ruokinta; aminohapot; lysiini; pigs; amino acids; feeding